New type of capillary for use as ion beam collimator and air-vacuum interface - Stoytschew, Valentin (2016)
Glass capillaries offer a unique way to combine small diameter ion beam collimation with an air-vacuum interface for ambient pressure ion beam applications. Usually they have an opening diameter of a few microns, limiting the air inflow sufficiently to maintain stable conditions on the vacuum side. As the glass capillaries generally are quite thin and fragile, handling of the capillary in the experiment becomes difficult. They also introduce an X-ray background produced by the capillary wall material, which has to be shielded or subtracted from the data for Particle Induced X-ray Emission (PIXE) applications. To overcome both drawbacks, a new type of conical glass capillary has been developed. It has a higher wall thickness eliminating the low energy X-ray background produced by common capillaries and leading to a more robust lens. The results obtained in first tests show, that this new capillary is suitable for ion beam collimation and encourage further work on the capillary production process to provide thick wall capillaries with an outlet diameter in the single digit micro- or even nanometre range.